Reform of the «Academia de la Magistratura» in Peru - Romero Osorio, Jorgeluis Alan (2020)
The «Academia de la Magistratura» has been a transformative factor which has positively impacted the judicial and prosecutor systems. Lesser levels of corruption have been recorded since its creation. The «Academia de la Magistratura» is a judicial training academy dedicated to the advancement of judges of the Judicial system and public prosecutors only. It is proposed the fusion of this institution with the «Junta Nacional de Justicia» because it will provide the legal instruments to create a new institution: The «Escuela Judicial Peruana».